The Nordic Common Data Element repository for describing cancer data. (11th November 2009) - Jonsdottir, Thora; Thorsson, Johann; Hvannberg, Ebba Thora; Litton, Jan-Eric; , Helgi Sigurdsson
The aim of the Nordic Common Data Element Project is to facilitate convergence towards a common metadata standard in cancer in the Nordic countries. The experience of installing, learning and using the open software suite, Cancer Data Standards Repository (caDSR), developed by the National Cancer Institute's Center for Bioinformatics, NCICB, in the USA is reported. The caDSR is a metadata repository including Common Data Elements (CDE) used by NCI-sponsored organisations. The object of this work is to develop a database of metadata for medical data elements, referred to as the Nordic Common Data Element Project (NCDEP) and to establish a common classification of data elements used in daily clinical practice and trials. The experience using the tools to define data elements for a Pathology Report (PR) for breast cancer is reported, along with how the tools were used to define alternative values and definitions in Icelandic.